Produk Akad Musyarakah Pada Bank Syariah Indonesia Mencerminkan Kemitraan Bisnis Yang Berbasis Prinsip Bagi Hasil Adil - Ajirna Ajirna; Bella Silvia; Nurul Astiva Nasution; Waldyansyah Waldyansyah; Husni Kamal (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
This study aims to analyze product innovations in the Musyarakah contract applied by Islamic financial institutions in Indonesia. The research uses a qualitative descriptive method with case studies from several Islamic banks. Data were collected through documentation and interviews with practitioners. The study found that innovations in Musyarakah products are largely driven by the need to enhance competitiveness and address the unique demands of the Indonesian market, particularly among micro, small, and medium enterprises (MSMEs)  Several banks have modified the classical Musyarakah structure to align with customer preferences and regulatory standards. For instance, some institutions implement tiered profit-sharing mechanisms, structured financing tenures, and integration with digital banking platforms to improve accessibility and monitoring. In addition, hybrid contracts that combine Musyarakah with other contracts, such as Ijarah or Murabahah, are increasingly used to create more flexible and customer-friendly financing solutions. Practitioners interviewed noted that one of the main challenges in implementing Musyarakah-based products is the higher operational and monitoring cost, due to the nature of partnership-based risk-sharing. However, these challenges are being addressed through technological innovation, such as mobile applications that help track business performance and automate profit-sharing calculations. The study concludes that product innovation in Musyarakah financing can enhance the inclusivity and effectiveness of Islamic banking in Indonesia, especially in supporting entrepreneurial sectors. Nevertheless, standardization, regulatory support, and continued investment in human resource capacity remain critical for sustained innovation. Future research may explore the customer perception of Musyarakah products, the impact of these innovations on financial performance, and comparative studies with conventional financing models.